Den uforløste hjemve : Marsklandets mørke natur i Theodor Storms Skimmelrytteren - Hoeck, Jonas M. (Academic Quarter | Akademisk kvarter, 2020)
Since the romantic era, man’s relationship with nature has been connected with strong emotions and ideas, and not all kinds of landscapes are therefore considered equally pretty or nice today. Through an ecocritical reading of the North German author Theodor Storm’s novella the The Rider on the White Horse (Der Schimmelreiter) (1888), this article illustrates why the North Frisian and Danish marshlands have been depicted as an uncanny (unheimliche) place in modern culture, and why this peripheral nature never became an integral part of what we today consider as the Danish landscape.